Involuntary resettlement in Jamuna bridge project: impoverishment risks and reconstruction measures - Ahsan, Md. Quamrul (BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master of Development Studies, 2007.